Indirect tephra volume estimations using theorical models for some Chilean historical volcanic eruptions with sustained columns - Romero, Jorge (2013)
Actually, the estimation of the volumes of fallout deposits gave us the possibility to determine a series of eruptive parameters, which are also accepted to classify the magnitude and intensity of those eruptions. If most of volumes are determined by field methods, other indirect (theorical) calculations on tephra fall deposit are based in complex physical characteristics of the eruptive column and plume dynamics and could help us to determine those characteristics. In the present investigation we obtained two new tephra volumes for recent and historical eruptions in Chile and we also compare some of them with well studied cases.